Let f and g be the functions whose graphs are shown below.
(a)Let u(x) = f (x)g(x). Find u'(3).(b)Let v(x) = g(f (x)) . Find v'(−2).
a) u '(x) = f '(x)g(x) + g '(x)f(x) [By using product rule of differentiation]. So u '(3) = f '(3)g(3) + g '(3)f(3) . Note... View the full answer
- a) A appears to be wrong. :(
- May 14, 2018 at 5:12pm
- Really sorry to hear that. I made a mistake in calculating g '(3) in part a). Actually the value of g '(3) = -(1/4). Hence u '(3)= -1. This is the final answer. Actually the diagram you gave is too small to see. Anyways I hope this answers your question. Thanks.
- May 15, 2018 at 12:57am